L-Lactic Acid Production by Lactobacillus rhamnosus ATCC 10863 - Ana Lívia Chemeli Senedese; Rubens Maciel Filho; Maria Regina Wolf Maciel (The Scientific World Journal)
Lactic acid has been shown to have the most promising application in biomaterials as poly(lactic acid). L. rhamnosus ATCC 10863 that produces L-lactic acid was used to perform the fermentation and molasses was used as substrate. A solution containing 27.6 g/L of sucrose (main composition of molasses) and 3.0 g/L of yeast extract was prepared, considering the final volume of 3,571 mL (14.0% (v/v) inoculum). Batch and fed batch fermentations were performed with temperature of 43.4°C and pH of 5.0. At the fed batch, three molasses feed were applied at 12, 24, and 36 hours. Samples were taken every two hours and the amounts of lactic acid, sucrose, glucose, and fructose were determined by HPLC. The sucrose was barely consumed at both processes; otherwise the glucose and fructose were almost entirely consumed. 16.5 g/L of lactic acid was produced at batch and 22.0 g/L at fed batch. Considering that lactic acid was produced due to the low concentration of the well consumed sugars, the final amount was considerable. The cell growth was checked and no substrate inhibition was observed. A sucrose molasses hydrolysis is suggested to better avail the molasses fermentation with this strain, surely increasing the L-lactic acid.